An investigation of Nitrospira bacteria in coastal wetlands of China: distribution pattern and related environmental driving factors - Zhao, Qiang; Sun, Dongyao; Tang, Xiufeng; Hou, Lijun; Liu, Min; Han, Ping (Frontiers in Marine Science, 2023)
Nitrate is mainly converted via aerobic nitrite oxidation during the second step of nitrification, which is catalyzed by nitrite-oxidizing bacteria (NOB) and the recently discovery complete ammonia oxidizers (comammox). Members of the genus Nitrospira are the most diverse and widespread known NOB and comammox. However, the distribution community assembly of Nitrospira in estuarine tidal flatestuary and coastal wetland and the major environmental shaping factors drivers affecting their abundance and diversity remain unknownunderstudied. Here in this study, we investigated present a large-scale investigation on the geographical distribution pattern of Nitrospira along the large-scale coastal wetlands of China. The results showed that the abundance of Nitrospira ranged from 4.96×10 6 -3.88×10 7 copies/g dry sediment, significantly ( (more than one order of magnitude) higher than amoA gene of ammonia-oxidizers.The identified Nitrospira belong to Nitrospira lineage Ⅳ (50%), lineage Ⅰ and Ⅱ. The adaptability of the three lineages to environmental factors (such as temperature, pH, salinity and particle size) are different, which leads to the diversity of its distribution composition in different estuaries. Network analysis showed that the cooperation takes greater portion than competition in the relationship of Nitrospira population. This study revealed the existence, abundance and community composition distribution of Nitrospira bacteria, as well as the major environmental driving environmental factors in estuarine ecosystems, which deepens our understanding of the niche separation of Nitrospira with the nitrogen cycling.